Exploration of interaction mechanism of tyrosol as a potent anti-inflammatory agent. Issue 2 (22nd January 2020) - Yadav, Tara Chand; Kumar, Naresh; Raj, Utkarsh; Goel, Nidhi; Vardawaj, Pritish Kumar; Prasad, Ramasare; Pruthi, Vikas
Abstract: Drug discovery for a vigorous and feasible lead candidate is a challenging scientific mission as it requires expertise, experience, and huge investment. Natural products and their derivatives having structural diversity are renowned source of therapeutic agents since many years. Tyrosol (a natural phenylethanoid) has been extracted from olive oil, and its structure was confirmed by elemental analysis, FT-IR, FT-NMR, and single crystal X-ray crystallography. The conformational analysis for tyrosol geometry was performed by Gaussian 09 in terms of density functional theory. Validation of bond lengths and bond angles obtained experimentally as well as theoretically were performed with the help of curve fitting analysis, and values of correlation coefficient ( R ) obtained as 0.988 and 0.984, respectively. The charge transfer within the tyrosol molecule was confirmed by analysis of HOMO→LUMO molecular orbitals. In molecular docking with COX-2 (PDB ID: 5F1A), tyrosol was found to possess satisfactory binding affinity as compared to other NSAIDs (Aspirin, Ibuprofen, and Naproxen) and a COX-2 selective drug (Celecoxib). ADMET prediction, drug-likeness and bioactivity score altogether confirm the lead/drug like potential of tyrosol. Further investigation of simulation quality plot, RMSD and RMSF plots, ligands behavior plot as well as post simulation analysis manifest the consistency of 5F1A-tyrosol complex throughout the 20 ns molecular simulation process that signifies its compactness and stability within the receptor pocket. Abbreviations: ADMET Absorption, Distribution, Metabolism, Excretion and Toxicity Å Angstrom COX-2 Cyclooxygenase-2 DFT Density Functional Theory DMF Dimethylformamide FMO Frontier Molecular Orbital FT-IR Fourier-transform Infrared Spectroscopy FT-NMR Nuclear Magnetic Resonance Spectroscopy HOMO Highest Occupied Molecular Orbital LUMO Lowest Unoccupied Molecular Orbital MD Molecular Dynamics NS Nanosecond NSAIDs Non-steroidal anti-inflammatory drugs OPE Osiris Property Explorer RMSD Root-Mean-Square Deviation RMSF Root Sean Square Fluctuation Communicated by Ramaswamy H. Sarma Abstract :